Impact of cerebral cardiopulmonary resuscitation maneuvers in a general hospital: prognostic factors and outcomes - Bartholomay, Eduardo; Dias, Fernando Suparregui; Torres, Fábio Alves; Jacobson, Pedro; Mariante, Afonso; Wainstein, Rodrigo; Silva, Renato; Bodanese, Luiz Carlos (Arquivos brasileiros de cardiologia, 2003)
To assess survival of patients undergoing cerebral cardiopulmonary resuscitation maneuvers and to identify prognostic factors for short-term survival. Prospective study with patients undergoing cardiopulmonary resuscitation maneuvers. The study included 150 patients. Spontaneous circulation was re-established in 88 (58%) patients, and 42 (28%) were discharged from the hospital. The necessary number of patients treated to save 1 life in 12 months was 3.4. The presence of ventricular fibrillation or tachycardia (VF/VT) as the initial rhythm, shorter times of cardiopulmonary resuscitation maneuvers and cardiopulmonary arrest, and greater values of mean blood pressure (BP) prior to cardiopulmonary arrest were independent variables for re-establishment of spontaneous circulation and hospital discharge. The odds ratios for hospital discharge were as follows: 6.1 (95% confidence interval [CI] = 2.7-13.6), when the initial rhythm was VF/VT; 9.4 (95% CI = 4.1-21.3), when the time of cerebral cardiopulmonary resuscitation was < 15 min; 9.2 (95% CI = 3.9-21.3), when the time of cardiopulmonary arrest was < 20 min; and 5.7 (95% CI = 2.4-13.7), when BP was > 70 mmHg. The presence of VF/VT as the initial rhythm, shorter times of cerebral cardiopulmonary resuscitation and of cardiopulmonary arrest, and a greater value of BP prior to cardiopulmonary arrest were independent variables of better prognosis.